Detection and enumeration of virulent Yersinia enterocolitica in food by DNA colony hybridization. - Hill, W E (1983)
A portion of a 44-megadalton plasmid found in Yersinia enterocolitica 8081 was used as a genetic probe to differentiate virulent and nonvirulent strains of the species. A DNA colony hybridization technique was employed. Three BamHI restriction endonuclease fragments labeled with 32P by nick translation were hybridized to lysed colonies of pure cultures, mixtures of virulent and nonvirulent cells, and portions of a food sample artificially contaminated with virulent Y. enterocolitica. The results of the colony hybridization test for virulence were the same as those obtained by the autoagglutination and suckling mouse tests. DNA colony hybridization detects pathogenic Y. enterocolitica in foods without the need for enrichment or pure cultures.